Write 9x - 3y = -6 in slope-intercept form. Make sure you show all steps and inverse operations
Answer:
y = 3x + 2 is the slope-intercept form of given equation 9x - 3y = -6
Solution:
Given that we have to write 9x - 3y = -6 in slope intercept form
The slope intercept form is given as:
y = mx + c
Where "m" is the slope of the line and "c" is the y - intercept
Let us convert the given equation into slope intercept form
9x - 3y = -6
Keep the variable "y" on one side and move the remaining terms to other side
9x + 6 = 3y
3y = 9x + 6
Move the coefficient of "y" from L.H.S to R.H.S
![y = (1)/(3)(9x + 6)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/jeut9u9a9pbd7una2upwoh8uhgv1rjoyu4.png)
Distribute
to terms inside bracket
![y = (1)/(3) * 9x + (1)/(3) * 6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ajljpp4mt6fu9cdwxpvpy2njkfzvlv67ff.png)
Simplify the above equation
![y = 3x + 2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/92d5g4hfat57bzucypg13t2cwdkd0ohcep.png)
Thus the slope intercept form is found